2012
DOI: 10.1080/02635143.2012.732059
|View full text |Cite
|
Sign up to set email alerts
|

Genetics at school level: addressing the difficulties

Abstract: Background: A wide range of studies has offered suggestions why genetics is difficult and some of their key findings are summarised. Underpinning all of this is the way the brain works when handling information. The limitations of working memory capacity offer an interpretation of these difficulties Purpose: The aim is to confirm that working memory capacity (and the related concept of field dependency) controls performance in understanding genetics and whether it is possible to improve performance by changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 76 publications
0
13
0
3
Order By: Relevance
“…All four teachers used mostly declarative content knowledge to teach the definitions and explain the genetics concepts of chromosomes, genes and alleles. These concepts are known to be problematic and students find them hard to grasp and distinguish (Chu & Reid, 2012). Predominant use of declarative knowledge was supposedly influenced by the biology syllabus, which required students to know only definitions of these concepts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All four teachers used mostly declarative content knowledge to teach the definitions and explain the genetics concepts of chromosomes, genes and alleles. These concepts are known to be problematic and students find them hard to grasp and distinguish (Chu & Reid, 2012). Predominant use of declarative knowledge was supposedly influenced by the biology syllabus, which required students to know only definitions of these concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the country"s chief examiners" biology performance reports highlight the fact that school genetics is one area in which candidates have consistently performed abysmally over the years (ECOS, 2008(ECOS, , 2009(ECOS, , 2012. Genetics is a topic that research has shown students tend to struggle with worldwide (Chu & Reid, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…I motsats till den tidigare forskningen (t.ex. Chu & Reid, 2012;Kibuka-Sebitosi, 2007;Lewis & Kattmann, 2004;Tsui & Treagust, 2010) ansåg ingen av de undersökta att genetik är mycket svårt, inte ens de 14 som fått två eller färre poäng i testet. Däremot tyckte 28 % att genetik är mycket lätt eller lätt, bland dem även de två studerande som endast fått en poäng i testet.…”
Section: Svårighetsgraden I Genetik Enligt Gymnasiestuderandeunclassified
“…I motsats till tidigare forskningsresultat (t.ex. Chattopadhyay, 2005;Chu & Reid, 2012;Gericke & Hagberg, 2007;Kibuka-Sebitosi, 2007;Lewis & Kattmann, 2004;Rotbain, Marbach-Ad & Stavy, 2006;Tsui & Treagust, 2010) ansåg de 46 gymnasiestuderandena att genetik inte är svårt, trots att endast fyra av dem kunde svara rätt på samtliga frågor.…”
Section: Slutdiskussionunclassified
See 1 more Smart Citation